Crossfire - Francis, Dick.; Francis, Felix (New York : G.P. Putnam's Sons, 2010)
Returning to his estranged mother's house for the first time since he joined the army at seventeen, Captain Tom Forsyth discovers that she is being blackmailed and sets out to discover and defeat this hidden enemy using his finely honed military skills.
Keywords: Soldiers -- Great Britain -- Fiction; Amputees -- Fiction; Homecoming -- Fiction; Race horses -- Training -- Fiction; Extortion -- Fiction; Tax evasion -- Fiction